Inoculation with Native Bradyrhizobia Strains Improved Growth of Cowpea Plants Cultivated on a Saline Soil. Issue 19 (27th October 2016) - Gómez Padilla, E.; Ruiz-Díez, B.; Fernández-Pascual, M.; López Sánchez, R.; Bloem, E.; Eichler-Löbermann, B.
ABSTRACT: Selection of osmotolerant rhizobia gained importance because of increasing soil salinity in many regions. A field experiment in the Cauto Valley was conducted to determine the effect of seed inoculation with two native strains of Bradyrhizobium sp. on biological nitrogen (N)-fixation of cowpea ( Vigna unguiculata ) on a salt affected soil. Inoculation with both strains resulted in higher numbers of nodules, specific N-fixation, and yields of cowpeas than the control without inoculation. The strain VIBA-1 ( Bradyrhizobium liaoningense ) was partly superior to VIBA-2 ( Bradyrhizobium yuanmingense ). This study indicates that the strains inoculated are competitive against other natural strains and able to nodulate cowpea.